Genetic and environmental factors in hypospadias. Issue 9 (September 1990) - Stoll, C; Alembik, Y; Roth, M P; Dott, B
Abstract : A case control study of hypospadias was performed from 1979 to 1987 in Alsace, north-eastern France. A total of 176 out of 60 847 male infants had hypospadias giving a prevalence at birth of 2.89 per 1000 male newborns; 15.3% of all infants with hypospadias also had other malformations. Renal and urinary tract malformations were present in 37.0% of the infants with hypospadias and other additional malformations. None of the numerous aetiological factors which were studied was correlated with hypospadias except low weight of the placenta. The recurrence risk for brothers was 17.0% (an empirical risk of about 1 in 6) and the heritability coefficient was 56.9%. First degree relatives of infants with hypospadias had more malformations other than hypospadias than controls. These results have to be taken into consideration for genetic counselling.